Tuning of optical and electrical properties of polyaniline on flexible cellulose through Eosin Y dye interaction. (5th April 2019) - Sarkar, Kamanashis; Deb, Krishna; Bera, Arun; Debnath, Ajit; Saha, Biswajit
Abstract: Polyaniline, which is an attractive macromolecular system for electronic applications, has been chosen in this work in order to bring a tuning and alignment of energy levels for controlling its electrical and optical properties through Eosin Y dye interaction. Polyaniline has been synthesized over flexible cellulose substrate through a very simple oxidative chemical vapor polymerization technique. Prepared polyaniline incorporated cellulose was then allowed to interact with the anionic dye of Eosin Y to control its charge transport and optical properties. The dye interaction leads to better crystallinity of polyaniline over cellulose as revealed from x-ray diffraction pattern. From optical characterization, a remarkable change of band gap varying from 2.629 eV to 2.471 eV has been observed with increasing dye interaction time. The effects of dye interaction on charge transport and carrier dynamics were studied from I-V curve, which shows an excellent improvement of electrical conductivity. The color generating chromophores present in dye are likely to interact with positively charged polaron defect states present in polyaniline. Thus it opens a wider and simpler way of functionalizing π -conjugated polymers on flexible cellulose substrate in exploring their applications as electronic materials in sensor, memory devices and field effect devices.